2013
DOI: 10.1165/rcmb.2012-0493oc
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Promotes Airway Epithelial ATP Release via Calcium-Dependent Vesicular Pathways

Abstract: ATP in airway surface liquid (ASL) controls mucociliary clearance functions via the activation of airway epithelial purinergic receptors. However, abnormally elevated ATP levels have been reported in inflamed airways, suggesting that excessive ATP in ASL contributes to airway inflammation. Despite these observations, little is known about the mechanisms of ATP accumulation in the ASL covering inflamed airways. In this study, links between cystic fibrosis (CF)-associated airway inflammation and airway epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
2
28
0
1
Order By: Relevance
“…If baseline mucin secretion is an important secretory modality under control conditions, as the results above suggest, it is also important to know whether or not it is increased during the mucous metaplasia, hyperplasia, and/or hypertrophy commonly associated with inflammatory conditions in the airways [ 2 ]. To test the potential relationship in HBECCs between mucin stores and baseline secretion we compared the output of mucins from cultures grown under control conditions with those in which inflammatory mucous hyperplasia/hypertrophy was induced by a supernatant of mucopurulent material (SMM; [ 41 43 ]), collected and prepared from lungs removed from patients with Cystic Fibrosis during organ transplant surgeries. SMM is a protein-rich, incompletely characterized ‘broth’ containing a multiple cytokines, nucleotides, and proteases that together induce a massive upregulation of mucin gene expression and mucous hyperplasia in HBECCs (e.g., see Fig 5 in Ref [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…If baseline mucin secretion is an important secretory modality under control conditions, as the results above suggest, it is also important to know whether or not it is increased during the mucous metaplasia, hyperplasia, and/or hypertrophy commonly associated with inflammatory conditions in the airways [ 2 ]. To test the potential relationship in HBECCs between mucin stores and baseline secretion we compared the output of mucins from cultures grown under control conditions with those in which inflammatory mucous hyperplasia/hypertrophy was induced by a supernatant of mucopurulent material (SMM; [ 41 43 ]), collected and prepared from lungs removed from patients with Cystic Fibrosis during organ transplant surgeries. SMM is a protein-rich, incompletely characterized ‘broth’ containing a multiple cytokines, nucleotides, and proteases that together induce a massive upregulation of mucin gene expression and mucous hyperplasia in HBECCs (e.g., see Fig 5 in Ref [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…We identified a mechanism for amplification of rhinovirus-induced airway inflammation by MUC5AC through release of ATP, a danger signal that is released during infection and contributes to nucleotide receptor-dependent inflammatory responses 32 . This mechanism was suggested in a previous study that indicated that administration of sterile supernatants of mucopurulent material from subjects with cystic fibrosis can induce ATP release by human bronchial epithelial cells in vitro 20 . The role of ATP as a potential driver of airway inflammation in stable asthma and COPD is well recognised 33,34 .…”
Section: Muc5ac In Inhibiting Anti-bacterial Responses During Virus Imentioning
confidence: 81%
“…Given our prior observations that Muc5ac deletion was anti-inflammatory, while augmentation with exogenous MUC5AC protein in mice had broad pro-inflammatory effects, we reasoned that this mucin could be mediating its effects via a danger signal that promotes inflammatory mediator release and cell recruitment. A previous study demonstrated that supernatants of mucopurulent material from subjects with cystic fibrosis can induce epithelial release of extracellular adenosine triphosphate (ATP) 20 , a well-recognised promoter of inflammation 21 that is also virus-inducible 22 . We therefore hypothesised that MUC5AC exerts its pro-inflammatory effects during RV infection via induction of extracellular ATP and examined the effect of ATP neutralisation using the ATP-hydrolysing enzyme apyrase in exogenous MUC5AC-treated RV-infected mice (Fig 5a).…”
Section: Muc5ac Exerts Pro-inflammatory Effects Via Extracellular Atpmentioning
confidence: 99%
“…In this reaction ATP is the missing factor and becomes available after cell lysis. Furthermore, it has been described that cellular stress due to inflammation [24] or hypotonic swelling in lung epithelial cells [25], leads to active ATP release. Hypotonic swelling might also occur during thawing, upon removal of the CPA solution.…”
Section: Discussionmentioning
confidence: 99%